Effect of FOXP2 transcription factor on immune infiltration of thyroid cancer and its potential clinical value - Xu, Lianghui; Yang, Zheyu; Zhao, Qiwu; Feng, Haoran; Kuang, Jie; Liu, Zhuoran; Chen, Linxie; Zhan, Lin; Yan, Jiqi; Cai, Wei; Qiu, Weihua (Frontiers in Immunology, 2022)
Background The clinical outcomes are not always favorable in certain thyroid cancer patients. The effect of Forkhead-box family on immune cells infiltration and tumor microenvironment in thyroid cancer was explored. The role of FOXP2 in tumor invasion and recurrence was investigated consequently. Methods TIMER and GEPIA were firstly employed to compare FOXPs expression in normal and cancer tissues from multiple human cancers. The results from database were confirmed by quantitative Real Time-PCR and Western blot in matched thyroid cancer and adjacent normal tissues, in addition to a panel of thyroid cancer cell lines and normal thyroid cell. GEPIA platform was employed to discover the possibility of FOXPs as prognostic indicator. TISIBD and UACLCAN were then employed to estimate the influence of FOXPs on lymph node metastasis and tumor staging. GEPIA analysis was initially employed to analyze correlation of FOXPs and tumor immune infiltrating cells, and TIMER dataset was then included for standardization according to tumor purity. Result Different member of FOXPs showed divergence in expression in various cancer tissues. Lower FOXP1, FOXP2 and higher FOXP3, FOXP4 levels could be identified in thyroid cancer tissues when compared with matched normal tissue. There was an inverse correlation between FOXP2, FOXP4 and immune invasion, whereas FOXP1 and FOXP3 were positively correlated. FOXPs showed remarkable correlations with multiply immune cells. More importantly, only FOXP2 showed the significant effect on recurrence and tumor staging. Conclusion As immune regulatory factor, the reduction of FOXP2 may affect tumor microenvironments and immune cells infiltration, enhance tumor immune escape, and promote recurrence of thyroid cancer. FOXP2 could be a new potential diagnostic and prognostic marker.